Spaceborne mid and farinfrared observations improving nighttime ice cloud property retrievals - Saito,M; Yang,P; Huang,X; Brindley,HE; Mlynczak,MG; Kahn,BH (Geophysical Research Letters, 2020)
Two upcoming missions are scheduled to provide novel spaceborne observations of upwelling farinfrared spectra. In this study, the accuracy of ice cloud property retrievals using spaceborne middletofarinfrared (MIRFIR) measurements is examined toward a better understanding of retrieval biases and uncertainties. Theoretical sensitivity studies demonstrate that the MIRFIR spectra are sensitive to ice cloud properties, thereby providing a robust means for retrieving cloud properties under nighttime conditions. However, the temperature dependence of the ice refractive index and relevant ice particle shape models need to be incorporated into the retrieval procedure to avoid systematic biases in inferring cloud optical thickness and effective particle radius. Furthermore, prior information of subpixel cloud fractions is essential to mitigation of substantial systematic retrieval biases due to inconsistent subpixel cloud fractions.